A pervasive computing architecture fostering integration in patient centred communities of care. (10th March 2009) - Cabitza, Federico; Locatelli, Marco P.; Sarini, Marcello; Simone, Carla
The paper shows how a pervasive computing architecture, CASMAS, and its associated modelling language can be used to support cooperation among the members of a patient-centred community of care and their digital devices. We also show how CASMAS can be augmented by the WOAD framework, which was developed independently to model and express declarative mechanisms of provision of awareness promoting information (API) in document-mediated communities. Parts of these mechanisms can be modelled on the basis of integrated care pathways taken from the medical specialist literature. We take the distributed hypertension monitoring case as an exemplifying and sufficiently complex scenario to show the feasibility and advantages of our semantically informed and modular approach. The scenario is then declined in terms of architectural components and cooperation-oriented mechanisms that are shared between the devices and entities of the designed community of care.